Teaching-Learning Environment and Internal Efficiency in Public Lower Secondary Schools in Kicukiro District, Rwanda - Muhizi Patrick; Dr Marha Nduta Kiarie (International Journal of Social Science and Human Research, 2026)
This study investigated learning environment and internal efficiency in public lower secondary schools in Kicukiro District, Rwanda. However, the objective of the study was to examine the influence of learning environment on internal efficiency in public day lower secondary schools in Kicukiro District, Rwanda. The study was grounded in Ecological Systems Theory, with a conceptual framework outlining key indicators for both independent and dependent variables. Descriptive Survey with mixed methods integrating both quantitative and qualitative approaches was employed. A total population of 2282 was composed of 24 head teachers, 336 teachers and 1922 students. Slovin’s formula was used to calculate a sample size of 340 composed of 4 head teachers, 50 teachers, and 286 students. Schools were selected using simple random sampling. After selecting schools, headteachers were selected using purposive sampling while teachers and students were selected using simple random sampling. Data collection tools involved questionnaires to gather data from teachers, interviews guide to gather data from head teachers, and focus group discussions to gather data from students. A reliability index of at least 0.7 was used as the benchmark to determine the reliability of the questionnaire, and a validity test was conducted with an acceptable threshold of 0.7. Quantitative analysis was conducted using SPSS version 26 descriptive statistics to calculate mean, standard deviation, frequency distribution and inferential statistics via regression analysis, while qualitative analysis was carried out through thematic coding. The study found that the teaching-learning environment had a moderate and statistically significant influence on internal efficiency (R² = 0.070), with safety, teacher support, and cooperative classroom practices contributing positively despite limited resources. The study concluded that strengthening the teaching-learning environment through improved classroom safety, enhanced teacher support, collaborative learning practices, and adequate learning resources would contribute to improving internal efficiency. The study recommended policy reforms and practices for balanced teacher deployment, professional development, infrastructure, and community partnerships, and suggests further research on school leadership and community resource management’s impact on internal efficiency.